PENGARUH PENERAPAN BERMAIN PEMBANGUNAN DALAM KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI TK IT NURUL IMAN PALEMBANG - Ana Zakiati Fakhiroh; Tutut Handayani; Yecha Febrieanitha Putri; Mardeli (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the problem of low fine motor skills in early childhood, which can be seen from the suboptimal development of these abilities. This condition occurs due to the limited and inconsistent stimulation provided. The purpose of this study is to determine the effect of developmental play on the fine motor skills of children aged 5–6 years at TK IT Nurul Iman Palembang. This study uses a quantitative approach with a pre-experimental method and applies a one-group pretest–posttest design. The population consists of all class B children aged 5–6 years at TK IT Nurul Iman, totaling 47 children, with a sample of 27 children. Data collection techniques include observation, tests, and documentation. Data analysis techniques consist of validity tests, reliability tests, normality tests, homogeneity tests, and hypothesis testing using the t-test. The results indicate that developmental play has a significant effect on children's fine motor skills, as shown by the obtained t-count value of -1.939, which falls within the rejection area of Ho. Thus, Ha is accepted, meaning that developmental play positively influences the fine motor skills of children aged 5–6 years at TK IT Nurul Iman Palembang.